Simultaneous Esthetic Crown Lengthening and Frenotomy Procedure for Smile Rejuvenation - Wijaksana, I Komang Evan; Pinatih, Made Talitha Suryaningsih; Krismariono, Agung (Journal of Indonesian Dental Association, 2022)
Introduction: Gingival tissue plays an important role in smile aesthetics, especially in the anterior maxillary region. A gummy smile (GS) is a gingival condition that appears excessive when the patient smiles. The prevalence of gummy smile in individuals aged from 20 to 30 is 10% of population. It is more common in women and can cause aesthetic problems. Gummy smile aetiology is multifactorial. This case report discusses gummy smile case caused by altered passive eruption (APE) and associated with the presence of aberrant frenum. Case Report: A 19-year-old female patient with chief complaints of the excessive gingival display. The diagnosis of the case was confirmed by clinically healthy gingiva in an intact periodontium with gummy smile due to the presence of altered passive eruption type I-B accompanied by an aberrant frenum. The final surgical plan was aesthetic crown lengthening (CL) with flap surgery and osteotomy simultaneous with a frenotomy. Conclusion: The aesthetic crown lengthening surgery and frenotomy can be performed simultaneously to correct the gummy condition and improve the patient’s smile profile. Appropriate examination, diagnosis, and treatment planning help achieve optimal patient outcomes.